TATA CARA PELAKSANAAN PENANGGUHAN PENAHANAN TERHADAP TERSANGKA DI LEMBAGA KEPOLISIAN BERDASARKAN KUHAP DAN PERATURAN PELAKSANAANNYA - Umi Enggarsasi; Atet Sumanto (Perspektif, 2005)
Detention pursuant to KUHAP is location or certain defendant in place by Investigator or public prosecutor or Judge with its stipulating, while reason to source the detention as arranged in Section 21 KUHAP mentioned that detention can be with the consideration for example, defendant felt concerned about to break away defendant felt concerned about will destroy eliminating evidence goods, and, defendant felt concerned about will again doing an injustice. Defendant can ask the detention deferment based on Section 31 KUHAP to police detention with the guarantee of money or people or on trust pursuant to condition determined, while such condition determined that is obliged to report, do not go out the house or town, and a period to detention deferment from defendant do not the inclusive of a period to prisoner status as arranged in KUHAP.